2015
DOI: 10.1111/ggi.12531
|View full text |Cite
|
Sign up to set email alerts
|

Associations between healthy lifestyles and health outcomes among older Koreans

Abstract: These results suggest that older Koreans with more healthy lifestyles are healthier than those with less healthy lifestyles. Also, the association between multiple healthy lifestyle factors and health outcomes is different by specific health outcome, showing different mechanisms between multiple healthy lifestyle factors and each health outcome. Geriatr Gerontol Int 2015; ●●: ●●-●●.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…The study sustained findings form previous research that better SRH was reported among people who smoked cigarettes and consumed alcohol [ 27 ]. However, this finding contradicted an earlier study that associated smoking and drinking with lower SRH scores [ 28 ] and another that found that the elderly with healthier lifestyles believed themselves to be healthier than those with less healthy lifestyles [ 29 ]. The participants in this study showed high incidence of unhealthy lifestyles; a little over one-fifth of them (20.39%) smoked.…”
Section: Discussioncontrasting
confidence: 81%
“…The study sustained findings form previous research that better SRH was reported among people who smoked cigarettes and consumed alcohol [ 27 ]. However, this finding contradicted an earlier study that associated smoking and drinking with lower SRH scores [ 28 ] and another that found that the elderly with healthier lifestyles believed themselves to be healthier than those with less healthy lifestyles [ 29 ]. The participants in this study showed high incidence of unhealthy lifestyles; a little over one-fifth of them (20.39%) smoked.…”
Section: Discussioncontrasting
confidence: 81%
“…74,75 Therefore, examination of the effects of multiple health behaviours on health outcomes is reasonable and worthwhile. Few studies (including two Chinese studies) have taken this approach, [76][77][78][79][80] and the Chinese studies were limited to a single geographic area (Hong Kong) 80 and setting (workplaces), 79 respectively. Previous research has revealed regional variation in residents' health behaviours due to differences in economic, cultural, and social contexts.…”
Section: Relationship Between Socio-demographic Factors and Health Oumentioning
confidence: 99%
“…Past research showed an association between practising several healthy lifestyle activities daily and reducing the risk of depression [13]. This same study suggested that sleeping for a proper duration, engaging in regular physical activity, and following abstemious drinking habits, which are all healthy lifestyle practices, could be essential for improving mental health.…”
Section: Plos Onementioning
confidence: 73%
“…Cross-sectional studies have shown that healthy lifestyle factors are positively associated with better mental health outcomes [ 13 ]. In that regard, the relationship between mental health conditions and lifestyle factors such as sleeping duration [ 14 ], habitual physical exercise [ 15 ], smoking habits [ 16 , 17 ], and alcohol consumption [ 18 ] have been studied to find methods of preventing mental illness.…”
Section: Introductionmentioning
confidence: 99%